MAKNA DAN STRUKTUR SASTRA LISAN DALAM MANTRA PENGOBATAN DI SUNGAILIAT KABUPATEN BANGKA - Nela Oktarina; Wardiah, Dessy; Nuzulia Armariena, Dian (Universitas PGRI Palembang, 2024)
The aim of this thought is to discover and present the structure and meaning of the verbal composition of the healing mantra of the Bhangka Sungailiat rule. The method used in this study can be a technique that seems subjective. Data collection techniques were carried out through presentations, interviews and recordings. The data discovery method for this thinking is the entity thinking strategy. The five most extreme individuals are used as data sources. The number of mantras analyzed were 15 mantras and their meaning and structure were analyzed. A look at the data reveals that Sungailiat's spell formula, 'Rule of Bangka', is important to have the most significant impact on projection, with 15 spells, including 3 spells, having a basic spell component. Keywords: Oral Literature, Medicine Spell, Meaning, Structure